2011
DOI: 10.1128/jcm.05290-11
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Gender-Associated Staphylococcus aureus spa Types Found among Nasal Carriers in a General Population: the Tromsø Staph and Skin Study

Abstract: Staphylococcus aureus nasal carriers risk autoinfection; however, knowledge about the factors that make specific strains successful colonizers is limited. This study was undertaken to identify the most successful S. aureus clones in nasal carriers and compare their distribution among host groups. The population structure of S. aureus isolates from healthy adults was investigated by spa typing 1,981 isolates from persistent and intermittent nasal carriers participating in a health survey. In the baseline screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
75
3
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 34 publications
(27 reference statements)
10
75
3
2
Order By: Relevance
“…Gender-specific spa types have been identified previously (Sangvik et al 2011). The study demonstrating this correlation was, however, larger than ours.…”
Section: Spa Type Distribution and Cluster Analysis (Papers III And Iv)contrasting
confidence: 55%
See 3 more Smart Citations
“…Gender-specific spa types have been identified previously (Sangvik et al 2011). The study demonstrating this correlation was, however, larger than ours.…”
Section: Spa Type Distribution and Cluster Analysis (Papers III And Iv)contrasting
confidence: 55%
“…There are indications that the immune defense is somehow boosted by female sex hormones (Marriott & Huet-Hudson 2006). This could explain the lower S. aureus colonization rates among females compared to males described in paper III and previous studies (Bischoff et al 2004;Herwaldt et al 2004;Sangvik et al 2011) as well as why the association between colonization and carriage status and serum concentration of vitamin D was more prominent among males (Olsen et al 2012). Due to the few hours of sun-light during the winter in Scandinavia, low serum concentrations of vitamin D, and thereby a higher prevalence of S. aureus, can be expected during this period.…”
Section: Prevalence Of S Aureus (Papers III and Iv)mentioning
confidence: 55%
See 2 more Smart Citations
“…spa type t084 is one of the most frequently found spa types among MSSA worldwide. In a study from Norway on 1113 MSSA isolates, t084 was shown to be the second most common spa type detected (7.6 %) [152]. Similarly, t084 is the second most abundant MSSA clone causing invasive infections in Europe [153].…”
Section: Paper IImentioning
confidence: 99%